The Age at Diagnosis of Autism Spectrum Disorder in Children in Japan - Shigeki Kurasawa; Kiyomi Tateyama; Ryoichiro Iwanaga; Taro Ohtoshi; Ken Nakatani; Katsushi Yokoi (International Journal of Pediatrics)
Background. No large-scale study of the timing of autism spectrum disorder (ASD) diagnosis has been performed in Japan to date. The aim of this study was to examine sex differences and annual trends in age at diagnosis of ASD using clinical data. Methods. Clinical data for children aged less than 18 years diagnosed with ASD between January 1, 2009, and December 31, 2013, and in whom follow-up was possible 1 year after diagnosis, were extracted. Results. The mean age at ASD diagnosis was 7.2 ± 4.2 years and the mode age was 3 years. No sex difference was observed for age at diagnosis (p=0.157). An annual trend of earlier diagnosis was observed when fiscal years were compared (p<0.001). Conclusion. This study highlighted the need to develop and provide appropriate early intervention methods and services for ASD children in Japan.